WEB-BASED TOUR PACKAGE INFORMATION SYSTEM ON BRADER BUS HOLIDAY BANDUNG TOUR - Khilda Nistrina; Rosmalina; Sutiyono; Denny Rusdianto (Institute of Computer Science (IOCS), 2022)
Tourism is a government priority because it has the potential to be one of the third largest contributors to national foreign exchange, thus the government's management of the tourism sector will continue to be improved. As a result, companies that provide travel services, often known as travel agents, have sprung up. At this time, the brader bus holiday bandung tour & travel is still conducting the registration, booking, payment, and cancellation of trip packages by manual. As a result, recording errors are common. Furthermore, prospective consumers must visit the office in order to select a tour package, implying that the work system is ineffective and inefficient. As a result, an information system is required to assist businesses in processing their data. The waterfall approach is used to build the information system, UML is used to design it, and PHP is used as the programming language and SQL server as the database management system. The study's findings have resulted in a web-based tour package booking information system that can make it easier for customers to order tours and for administrators to manage client data.